Analisis Keterbukaan Ekonomi Dan Ekspor Di Indonesia: Studi Empiris Pada Dampak Covid-19 Dan Peperangan Rusia-Ukraina - M. Aulia Rachman (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Global economic uncertainty due to the Covid-19 pandemic and the Russia-Ukraine war has had an impact on the supply chain of goods and services. In the midst of global economic turmoil, Indonesia's trade performance has had a positive average trade balance in the last 5 years. This study examines the impact of economic conditions on trade openness and exports in Indonesia, and assesses the impact of the Covid-19 pandemic and the Russia-Ukraine War. The research method used is ARDL to to examine the short-run and long-run effects of variables using monthly data from 2017 to 2022. The findings show that the Inflation variable has a positive impact on trade openness and exports in Indonesia, this contradiction with Romer's hypothesis and implies that the possibility of Indonesia's international trade is in line with the approach of the Ricardian model. The addition of Covid-19 cases has a negative impact on trade openness, while the pandemic period has a positive impact on exports. The variables of the Russia-Ukraine war have a negative but not significant impact. Policy recommendations are to maintain domestic productivity in order to maintain the needs of goods and services, as well as domestic and foreign supply chains